Long-term results of organ-preserving treatment of uterine leiomyoma combined with endometriosis. - V. I. Ivakh (Medičnì Perspektivi)
The analysis of a five-years’ catamnesis of reproductive age women who underwent surgery to remove leiomyoma nodes (myomectomy) is represented in this article. The aim of the study was to determine the incidence of tumor recurrence after myomectomy in women with leiomyoma combined with endometriosis. 82 operated patients, included into rescarch were divided into two groups according to the criterion of the presence or absence of endometriosis of the uterus. Group I included 44 (53.7%) cases of isolated lyomyomyoma surgery, and group II - 38 (46.3%) cases of combination of a similar tumor with endometriosis of the uterus. Myomectomy was performed by the transabdominal way in 43.9%, laparoscopic – in 46.3%, transcervical with a hysteroresectoscope - 11.4% of cases of operative treatment. According to the 5 years observation after the surgery, the recurrence of uterine leiomyoma appeared in 56.1% of women of both groups, while in group II, where the combination of uterine leiomyoma with endometriosis was noted, the frequency of tumor recurrences was significantly higher (71.1%, p<0,05%) than in group I with isolated uterine leiomyoma (43.2%,). Thus, the long-term results of myomectomy in women with uterine leiomyoma are associated with the risk of recurrence of the tumor in almost every second woman, but with the combined pathology of the uterus, these cases have a number of features compared to an isolated tumor – 2.5 times higher risk of recurrence in the first year after the operation and by 1.65 times higher frequency of relapse of the leiomyoma within 5 years after the surgery. The authors suggest that these differences evidence that the presence of endometriosis of the uterus is an additional factor that initiates the mechanisms of recurrence of the uterine leiomyoma after miomectomy, which should be taken into account in the development of a program of postoperative reproductive health rehabilitation of women with co-pathology of the uterus.